Modular and Reconfigurable Platform as New Philosophy for the Development of Updatable Vehicular Electronics - V. Cañas; A. García.; J. De las Morenas; J. Blanco (Revista Iberoamericana de Automática e Informática Industrial RIAI)
A new conception in the development of Electronic Control Units (ECUs), which are also called On-Board Units (OBUs), is discussed in this paper from an ontological vision oriented to the compatibility of vehicles with future technologies in the automotive field. This work also provides a new methodology in the design of On-Board vehicle units. The proposed technique is based on the concept of modular electronic units that can change their functionality depending on the modules they are consisted of. The study was initially designed at the theoretical level, analysing the problems in the sector in the face of the coexistence between vehicles today and those that are bound to appear in the near future, and that will incorporate capabilities making them connected and even autonomous. Additionally, a fully operational prototype has been developed so as to ascertain the possibilities of the proposed solution.